2019
DOI: 10.1111/ejh.13322
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias in hematopoietic stem cell transplantation: A systematic review and meta‐analysis

Abstract: Background: There are controversial data regarding the relationship between hematopoietic stem cell transplantation and arrhythmias. This meta-analysis was performed to evaluate the incidence of arrhythmias in patients following hematopoietic stem cell transplantation (HSCT). Methods: A literature search was conducted utilizing MEDLINE, EMBASE, andCochrane Databases from inception through April 2019. Pooled incidence with 95% confidence interval (CI) were calculated using random-effects meta-analysis. The prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…To date, studies examining AF after HCT have been limited to patients undergoing autologous HCT, [32][33][34][35][36][37][38] representing an older population with greater comorbidities and a higher proportion of pre-HCT cardiotoxic (eg, chest radiation and anthracyclines) exposures, compared with patients undergoing allogeneic HCT. To our knowledge, our study is the first to describe the incidence and risk factors for AF in a contemporary cohort of allogeneic patients, allowing us to capture evolving HCT practices (eg, expanding donor stemcell source, use of nonmyeloablative conditioning, increasingly older age at HCT, and expanded indications for HCT).…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies examining AF after HCT have been limited to patients undergoing autologous HCT, [32][33][34][35][36][37][38] representing an older population with greater comorbidities and a higher proportion of pre-HCT cardiotoxic (eg, chest radiation and anthracyclines) exposures, compared with patients undergoing allogeneic HCT. To our knowledge, our study is the first to describe the incidence and risk factors for AF in a contemporary cohort of allogeneic patients, allowing us to capture evolving HCT practices (eg, expanding donor stemcell source, use of nonmyeloablative conditioning, increasingly older age at HCT, and expanded indications for HCT).…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] A recent meta-analysis revealed that the estimated incidence of all types of arrhythmia following HCT was 7.20% (95% CI: 4.90–10.50), and the most common type was AF/AFL, with an estimated incidence of 4.20% (95% CI: 1.70–9.60). [ 22 ] In our study, the most common post-CCVD were also HF and arrhythmia (6.02% and 5.26%, respectively). Late post-CCVD was reported to be associated with chemotherapy toxicity, CVRFs, chronic graft- vs .-host disease, and long-term physical inactivity.…”
Section: Discussionmentioning
confidence: 51%
“…The incidence of early fatal cardiotoxicity during the first 100 days post-transplant was reported to be 0.90% to 10.00%, of which the most common events were HF and arrhythmia [21] . A recent meta-analysis revealed that the estimated incidence of all types of arrhythmia following HCT was 7.20% (95% CI: 4.90–10.50), and the most common type was AF/AFL, with an estimated incidence of 4.20% (95% CI: 1.70–9.60) [22] . In our study, the most common post-CCVD were also HF and arrhythmia (6.02% and 5.26%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular complications have been reported in this setting primarily as a result of cytokine release syndrome and complications [ 64 ]. The most common malignancy treated with autologous stem cell transplantation is multiple myeloma [ 65 ], which associates with cardiomyopathy and poor outcomes [ 55 , 66 69 ].…”
Section: Cardiotoxicities In Cardio-oncologymentioning
confidence: 99%